The Phenomenon Of “Women’s Prose”: History And Development - Obidova Farangiz Akmal qizi (Next Scientists International Journal EIJP, 2026)
The phenomenon of “women’s prose” occupies a significant place in world literature and literary criticism. Emerging from the broader struggle for women’s voices and rights, women’s prose reflects unique social, psychological, and aesthetic experiences shaped by gender. This article explores the historical origins, thematic features, stylistic characteristics, and major stages in the development of women’s prose from early literary traditions to contemporary global literature. Special attention is paid to the debates surrounding the term itself, its relationship to feminist criticism, and its relevance in modern literary discourse.